Maximal Eccentric Hamstrings Strength in Competitive Alpine Skiers: Cross-Sectional Observations From Youth to Elite Level - Franchi, Martino V.; Ellenberger, Lynn; Javet, Marie; Bruhin, Björn; Romann, Michael; Frey, Walter O.; Spörri, Jörg (Frontiers in Physiology, 2019)
Competitive alpine skiers are subject to substantial risks of injury, especially concerning the anterior cruciate ligament (ACL). During “landing back weighted” episodes, hamstrings may partially counteract the anterior shear force acting on the tibia by eccentrically resisting the boot-induced drawer of the tibia relative to the femur. The aim of the present study was to provide novel descriptive data and sport-specific reference values on maximal eccentric hamstrings strength in competitive alpine skiers from youth to elite level, and to explore potential relationships with sex, age and biological maturation. 170 competitive alpine skiers were investigated: 139 youth athletes (51 females, 88 males; age: 13.8 ± 0.59y) and 31 elite athletes (19 females, 12 males; age: 21.7 ± 2.8 y). Maximal eccentric hamstring strength (MEHS) was assessed by the Nordbord device (Nordbord, Albion, Australia). U15 female skiers presented lower MEHS compared to female elite skiers for both limbs (R= 209.5 ± 43.81 N vs. 339.8 ± 48.38 N, respectively, p<0.001, and L= 207.3 ± 46.47 N vs. 303.2 ± 35.02 N, respectively, p<0.001). Similarly, lower MEHS was observed in U15 male skiers compared to male elite skiers for both limbs (R= 258.7 ± 50.84 N vs. 486± 62.39 N, respectively, p<0.001, and L= 257.7± 57.24 N vs. 427.1 ± 53.62 N, respectively, p<0.001). Correlations between MEHS and chronological age were modestly significant only for the U15 group (r = 0.37, p<0.001). When the correlations for the U15 group were performed between MHES and maturity offset (obtained from the calculation of biological age, i.e. age at peak height velocity), statistical significance was reached by all the correlations run for 3 variables (Males<0: r = 0.59, p<0.0001; Males>0: r = 0.70, p<0.0001; and Females>0: r = 0.46, p<0.0001, start of maturity offset = 0). This cross-sectional description of MEHS in alpine skiers from youth to elite level highlights the importance of biological maturation for MEHS values in youth athletes and presents novel data that may offer insights into new approaches for injury prevention.